The molecular systematics of Ulva Linnaeus and Enteromorpha Link (Ulvales, Chlorophyta) from the South Western Cape, South Africa - Kandjengo, Lineekela (Department of Biological Sciences, 2014)
Bibliography : leaves 64-79.